Analisis Kebutuhan Pengembangan Sosial Emosional Anak Usia Dini di Era Digital - Siti Muhaimin Ibrahim; Bunga Alifa Antahari; Marselanda Hasan; Ningsi Mahmud; Dindayasnatia Dindayasnatia; Nurzia Ilahude; Fikra Mahyun; Annisa Fahmi Mannassai (Jejak digital: Jurnal Ilmiah Multidisiplin, 2026)
This study aims to analyze the needs for social-emotional development of early childhood in the digital era. The research used a qualitative approach with a descriptive research type. Data collection techniques were carried out through observation, interviews, and documentation. The research subjects consisted of teachers and parents of early childhood children. The results showed that the use of gadgets and digital media influences the social-emotional development of early childhood. Children who excessively use gadgets tend to be less active in social interactions, have difficulty controlling emotions, and prefer playing alone rather than with peers. However, digital technology can also provide positive impacts when used as an educational learning medium with proper guidance from parents and teachers. In addition, group play activities, active communication, and direct social interaction have proven to support children’s social-emotional development. Therefore, collaboration between parents, teachers, and early childhood education institutions is needed to supervise technology use and create a learning environment that supports optimal social-emotional development of early childhood in the digital era.